2021
DOI: 10.1155/2021/4572282
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-181b Serves as a Circulating Biomarker and Regulates Inflammation in Heart Failure

Abstract: Heart failure (HF) is the typical terminal stage of cardiac diseases involving inflammatory states. The function of microRNAs (miRNAs) in the progress of HF remains poorly understood. In this study, real-time PCR results showed a decreased expression of miRNA-181b (miR-181b) in HF patients compared with healthy individuals. Besides, miR-181b expressions were negatively correlated with hypersensitive C-reactive protein (hsCRP) levels in the serum of HF patients. Receiver operator characteristic (ROC) curve anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Compared with healthy people, the expression of MiR-181b in heart failure patients decreased, while the expression of hypersensitive C-reactive protein (hsCRP) levels increased. The expression of MiR-181b in heart failure rats was negatively correlated with IL-1, TNF-α, and IL-6 ( 61 ). Wang et al proved up-regulation of miR-335 reduced MI damage in rats by reducing oxidative stress, inflammation, and apoptosis, and MAP3K2 was an essential target for miR-335 to exert cardioprotection ( 62 ).…”
Section: Mirnas and Mechanism Of MImentioning
confidence: 99%
“…Compared with healthy people, the expression of MiR-181b in heart failure patients decreased, while the expression of hypersensitive C-reactive protein (hsCRP) levels increased. The expression of MiR-181b in heart failure rats was negatively correlated with IL-1, TNF-α, and IL-6 ( 61 ). Wang et al proved up-regulation of miR-335 reduced MI damage in rats by reducing oxidative stress, inflammation, and apoptosis, and MAP3K2 was an essential target for miR-335 to exert cardioprotection ( 62 ).…”
Section: Mirnas and Mechanism Of MImentioning
confidence: 99%
“…Evidence : MiR-155 level was measured in 13 studies [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Its overexpression was found mainly in MCI (5 studies) [ 10 , 13 , 14 , 19 , 21 ] and InfDCM (3 studies) [ 12 , 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only one study identified increased expression of miR-155 in ischemic cardiomyopathy [ 20 ]. The remaining studies did not detect increased miR-155 expression in other myocardial diseases (non-inflammatory DCM [ 11 , 12 , 17 , 18 , 19 ], rheumatic carditis [ 15 ], or hypertrophic cardiomyopathy [ 20 ]). Two studies performed ROC-AUC analysis, one for distinguishing between MCI and healthy subjects (AUC = 0.901) [ 13 ], and one for InfDCM and healthy subjects (AUC = 0.68) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-181b expression was suppressed before increasing TNF-α, IL-1β and IL-6 levels in the heart tissue of a rat model of HF induced by isoproterenol. miR-181b overexpression decreased TNF-α, IL-1β and IL-6 expression in a primary culture of rat neonatal cardiomyocytes [ 32 ].…”
Section: Inflammation and Mirnasmentioning
confidence: 99%